Analyzing Repair Organization in Single-Sex Classrooms: A Conversation Analysis Perspective - Ukhrowi, Wim Banu (EDUJ : English Education Journal, 2024)
This study investigates the repair organizations in English classrooms within a single-sex class. The bilingual school operates in an Islamic boarding environment, separating students by gender. A qualitative approach was employed, collecting data through classroom observations and video recordings across three sessions each in male-only and female-only classes. Analyzing the interactions through Paul Ten Have's interactional organization framework, especially the repair organization paradigm. Distinct patterns emerged, such as the teacher's dominant role in initiating repairs in both classes, although interaction fluidity and response styles varied due to differences in gender dynamics and teaching styles. This study highlights the nuanced influence of gender and cultural context on interaction patterns, specifically in repair organization within classroom discourse. Repair organization in female-only and male-only classes revealed distinct patterns over three meetings, influenced by interactional dynamics and gender-based classroom environments. In the female-only class, self-initiated self-repair initially increased, peaking at 50% in the second meeting before decreasing to 9% by the third. This decline was accompanied by a rise in other-initiated self-repair, indicating a shift toward more collaborative repair strategies. Conversely, the male-only class emphasized self-initiated self-repair at first, which declined as self-initiated other repair rose to 67% in the second meeting, reflecting a gradual move toward collaboration. By the final meeting, other-initiated self-repair dominated at 60%, showing a balance between self-reliance and peer support among male students. It can be summarized that there is a significance flow of repair organization both in female-only class students and male-only class students.